Sanksi Adat terhadap Krama Desa yang Melakukan Wanprestasi dalam Pengembalian Kredit Pada Lembaga Perkreditan Desa di Desa Adat Kapal - Anak Agung Ngurah Dharma Bayu Subandi; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2020)
Banks as credit providers should trust their customers within the agreed period of repayment of all credit that has been submitted. In practice, many customers do not fulfill the promised time to repay their loans. For various reasons, Default is caused the debtor's lack of awareness of his binding obligations. This study aims to determine the factors that lead to default in returning credit at the Desa Adat Kapal credit institution, and to determine the settlement of default in returning credit at the Desa Adat Kapal credit institution. The type of research used is the type of empirical research, where this research is carried out in accordance with the real situation of a community group or the surrounding environment in order to find facts or existing legal problems. The results of this study indicate that the factors causing non-performing loans in general are that all loans carry a high risk. Non-performing loans are loans that contain weaknesses or do not meet the quality standards set by the bank. Then, the settlement of defaults according to custom at the Ship Traditional Village Credit Institution is based on Article 8 of the Traditional Ship Village Credit Institution agreement.